If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=-11+3(c+5)
We move all terms to the left:
7-(-11+3(c+5))=0
We calculate terms in parentheses: -(-11+3(c+5)), so:We get rid of parentheses
-11+3(c+5)
determiningTheFunctionDomain 3(c+5)-11
We multiply parentheses
3c+15-11
We add all the numbers together, and all the variables
3c+4
Back to the equation:
-(3c+4)
-3c-4+7=0
We add all the numbers together, and all the variables
-3c+3=0
We move all terms containing c to the left, all other terms to the right
-3c=-3
c=-3/-3
c=1
| 4+22b=98 | | -8(-8+5)=5x-35 | | -24-4k=3(2+2k) | | 0=-16t^2+32t+10 | | 4=90-x | | 9v+4v=3 | | 12x–4=14x–10 | | 2(5x+2=10x+5 | | y–15=4y–3 | | 3x+7-7=-5=7 | | 5+14y=9y–5 | | -15+4n=-4n-7n | | -5-4y=-53 | | 260=20v | | (3x+8)+(7x-2)=106 | | 12=-14n | | 2(y-24)+4(y-4)=50 | | 5r+2=17 | | -2x+7=-5x-5 | | 12x-(8x-3)=7 | | b2=0 | | y/5=17/8 | | -1/3(6x-21)=-5 | | (4/5)2=x | | b-4/6=b2/2 | | 5x+6x–8x+2x=x+15 | | s=25+.25s | | 3k+9-2k=11 | | 47+(3x+22)+(6x+3)=180 | | 4-3x=2x-26 | | 4x-5x+11=2x-3 | | 1.6x+-3=1 |